Quality by Design (QbD) Approach in the Formulation of Liposomal Gel: A Review - Himabindu, Attuluri V S; Devi, Alla Seetha (Indian Journal of Pharmaceutical Education and Research)
Liposomal gels represent an advanced drug delivery system that combines the benefits of liposomal encapsulation with the controlled release properties of gels, offering enhanced therapeutic efficacy, stability and patient compliance. Quality by Design (QbD) is a systematic approach to pharmaceutical development, focusing on predefined objectives and emphasizing product and process understanding. This review explores the application of QbD principles in the formulation of liposomal gels, discussing key aspects such as defining the Quality Target Product Profile (QTPP), identifying Critical Quality Attributes (CQAs), Critical Material Attributes (CMAs) and Critical Process Parameters (CPPs) and the implementation of Design of Experiments (DoE) for optimization. The article also covers risk assessment, control strategies and the regulatory benefits of the QbD approach in ensuring consistent product quality. Challenges and future directions for the application of QbD in the development of liposomal gel formulations are also addressed.
Keywords: Critical Quality Attributes; Liposomes; Quality by Design; Risk Assessment